(untitled) (Economic journal of Lesya Ukrainka Volyn National University, 2018)
Coming out of the global financial crisis, businesses have fallen into a deeper one – a crisis of confidence. Trust and economic progress are closely interconnected, the more we trust each other, the better we can work together, the higher chances of economic growth. Low-credence organizations are uncompetitive, and vice versa, those based on high trust have better opportunities to achieve predictable business outcomes in rapidly changing and stressful conditions. Confidence between business partners increases the market value of the enterprise and its profitability, as high reputation is accompanied by a reduction in the cost of monitoring partners, which in turn contributes to beneficial for both contracting parties flexible interpretation of agreements where, as a result of incomplete information, the ability to foresee all scenarios for the development of events is limited. There is a correlation between employee empowerment and profitability. Extremely important is the impact of trust on transactional expenses, which include the cost of obtaining the necessary information on prices and quality of goods, negotiating, contracting, entering into agreements, monitoring of their execution and legal protection of the rights of the owner in case of violation. The trust in the client, employee, supplier and loyalty that results out of it has positive impact on the cost of their communication. Oral agreement instead of laborious negotiations gets real weight then, especially in situations where innovation-oriented changes are taking place. In all these cases, trust acts as a filler of gaps in mutual understanding. It can be easily destroyed by a desire to evaluate the staff. Regular assessments should be replaced by conversations between the supervisor and the subordinate employee about what each of them expects from another, and from the company as a whole, what needs to be done, so that they can perform their work better. Without trust, there can be no talk of a successful motivation of employees.